2020
DOI: 10.1039/c9dt04470a
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the active site triad: merging hemilability, proton responsivity, and ligand-based redox-activity

Abstract: Metalloenzymes catalyze important reactions by managing the proton and electron flux at the active site. In synthetic systems; hemilability, proton responsivity, and ligand-based redox-activity can be utilized as a bridge to harness this reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Our work has revealed that the polypyridyl ppq ligand is the major electron acceptor during sequential redox processes of the cobalt complex and that the Co intermediate with a triply reduced ppq radical ligand promotes the hydrogen evolution reaction. Even though the noninnocent redox properties of various ligands have been demonstrated, multiple redox forms of a polypyridine ligand bound to 3d transition metals are rarely characterized or discussed with respect to HER catalysts. , …”
Section: Introductionmentioning
confidence: 99%
“…Our work has revealed that the polypyridyl ppq ligand is the major electron acceptor during sequential redox processes of the cobalt complex and that the Co intermediate with a triply reduced ppq radical ligand promotes the hydrogen evolution reaction. Even though the noninnocent redox properties of various ligands have been demonstrated, multiple redox forms of a polypyridine ligand bound to 3d transition metals are rarely characterized or discussed with respect to HER catalysts. , …”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic systems and, in particular, metalloenzymes mediate a fascinating array of reactions via a carefully evolved secondary coordination sphere. Enzyme active sites leverage effects such as hydrogen bonding, electron transfer pathways, and electrostatic effects to precisely tune the reactivity of metallocofactors. ,,, One example illustrating the importance of the secondary coordination sphere is in oxidase chemistry. For example, the terminal oxidant in cytochrome P450 enzymes, Compound I, consists of an Fe­(IV)-oxo which is generated from O 2 via the delivery of proton and electron equivalents from cofactors and the protein superstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Transient coordination of a carboxylate additive (e.g., acetate, pivalate) is also a key feature of C–H activation catalysis. , The ligand switches from a κ 2 -O,O to κ 1 -O mode in order for the pendent oxygen to abstract a proton from the activated C–H bond, a mechanism that is commonly referred to as concerted-metalation deprotonation (CMD) or ambiphilic metal ligand activation (AMLA; Scheme b). , In this case, the carboxylate is ultimately a stoichiometric reagent, but there are many other examples of supporting ligands that can behave in both a structurally responsive and proton-responsive manner …”
Section: Structurally-responsive Ligands: Historic Background and Gen...mentioning
confidence: 99%
“…Recent reviews have focused on specific ligand types, such as versatile coordination pincers and hemilabile ligands with π-bonding moieties. , The current contribution showcases a variety of ligand types, that all modulate the reactivity of a metal by changing the coordination mode (Figure a). In nature, dynamic changes in the primary coordination sphere of metalloenzymes commonly influences function. Examples include amino acid residues that dissociate to open a site for substrate binding or to assist in proton and/or electron shuttling. For example, the function of Cytochrome c can switch from electron transfer to peroxidase due to changes bonding between iron and a methionine residue, which is one of the axial ligands (Figure b). , The mechanism that controls this switch in reactivity is complex and is still being elucidated. , However, it likely involves a weakening of the Fe–methionine interaction, coordination of a lysine residue to the axial site, and also an increased prominence of five-coordinate iron.…”
Section: Introductionmentioning
confidence: 99%